Shifts in leaf litter breakdown along a forestpastureurban gradient in Andean streams - Cueva Agila, A. (2016)
Tropical montane ecosystems of the Andes are critically threatened by a rapid land-use change which can potentially affect stream variables, aquatic communities and ecosystem processes such as leaf litter breakdown. However, these effects have not been sufficiently investigated in the Andean region and at high altitude locations in general. Here, we studied the influence of land-use (forest-pasture-urban) on stream physico-chemical variables (e.g. water temperature, nutrient concentration and pH), aquatic communities (macroinvertebrates and aquatic fungi) and leaf litter breakdown rates in Andean streams (southern Ecuador), and how variation in those stream physico-chemical variables affect macroinvertebrates and fungi related to leaf litter breakdown. We found that pH, water temperature and nutrient concentration increased along the land-use gradient. Macroinvertebrate communities were significantly different between land-uses. Shredder richness and abundance were lower in pasture than forest sites and totally absent in urban sites, and fungal richness and biomass were higher in forest sites than in pasture and urban sites. Leaf litter breakdown rates became slower as riparian land-use changed from natural to anthropogenically disturbed conditions, and were largely determined by pH, water temperature, phosphate concentration, fungal activity, and single species of leaf-shredding invertebrates. Our findings provide evidence that leaf litter breakdown in Andean streams is sensitive to riparian land-use change, with urban streams being the most affected. In addition, this study highlights the role of fungal biomass and shredder species (Phylloicus; Trichoptera and Anchytarsus; Coleoptera) on leaf litter breakdown in Andean streams and the contribution of aquatic fungi in supporting this ecosystem process when shredders are absent or present low abundance in streams affected by urbanization. Finally, we summarize important implications in terms of managing of native vegetation and riparian buffers to promote ecological integrity and functioning of tropical Andean stream ecosystems.